Ghost town [videorecording (DVD)] - Koepp, David; Koepp, David; Gervais, Ricky; Leoni, Téa, 1966-; Kinnear, Greg, 1963-; Wiig, Kristen, 1973- (DreamWorks Home Entertainment, 2008)
Bertram Pincus is an irritable dentist whose people skills leave much to be desired. Pincus dies unexpectedly, but is miraculously revived after seven minutes, he wakes up to discover that he now has the annoying ability to see ghosts. Even worse, they all want something from him. Frank Herlihy, in particular, pesters him into breaking up the impending marriage of his widow Gwen. Now, Pincus is put squarely in the middle of a triangle with spirited result.